A national survey of facilities for complainants of sexual assault. (April 2017) - Dhairyawan, Rageshri; Shardlow, Kate; Carroll, Michelle; Sacks, Rachel
In 2006, a national survey demonstrated wide disparities in services offered to sexual assault complainants in the UK, most marked between sexual assault referral centres and non-sexual assault referral centres (police victim examination suites). With national standards introduced in 2009 and the expansion of sexual assault referral centres, we aimed to evaluate the current situation. A questionnaire based on the original 2006 survey, collecting data on population covered, access, funding, personnel, medical care and clinical governance was sent to all 44 UK sexual assault referral centres open in 2012. No non-sexual assault referral centres were identified. Data were collected over six months from December 2012. Twenty-three sexual assault referral centres from England and Scotland responded (response rate 52%), but not all answered every question. All (20/20) had 24 h access for acute referrals, although one sexual assault referral centre reported 24 h opening was not always possible due to recruitment issues. Thirteen of 20 (65%) had a separate rota for under 16 s, but this was often not 24 h/day. All services (20/20) offered facilities for non-police referrals and for provision of anonymous intelligence. All sexual assault referral centres employed female examiners, 11/17 (65%) male examiners and half (10/20) forensic nurse practitioners. All (21/21) offered pregnancy testing and emergency contraception, 19/21 (90%) HIV post-exposure prophylaxis, 12/21 (57%) hepatitis B virus vaccine and 11/21 (52%) medical care for injuries on site. For follow-up care, 12/21 (57%) provided in house counselling, 10/21 (48%) sexually transmitted infection screening, 12/21 (57%) hepatitis B virus vaccination and 14/21 (67%) HIV post-exposure prophylaxis . Our survey shows improvement in services for complainants of sexual assault since 2006 with better access to forensic examinations, medical and psychological care. However, as the response rate was low and without data from non-sexual assault referral centre services, we cannot give a comprehensive national picture. Our results also show that there has been little improvement in providing sexual health screening on site or by referral and this should be addressed by sexual assault referral centres.